Study on the mechanical properties of composite wall covered with PVC eco-wood board. (2nd October 2020) - Li, Jiuyang; Fu, Weijia; Li, Fangqi; Li, Daozheng
Abstract: The use of PVC ecological-wood in composite wall is expected to provide the requirements of green and sustainable development. So bending performance experiment and tensile property test were done for the materials that makes up the PVC ecological-wood board. The stress–strain relations model, tensile properties, bending resistance characteristics of PVC ecological-wood board were proposed. Furthermore, uniform-loading test and low-cycle reversed loading experiment of the composite board were performed. Load deflection, ductility coefficient, strain analysis, determination of the yield and damage load of the wall were analyzed. It indicated that the wall possessed a relatively high load-bearing capacity, shearing capacity and lateral stiffness to a certain degree.